THE ROLE OF ONLINE LEARNING IN TEACHING HUMAN SCIENCES ON HIGHER EDUCATION - Jalgasova Laura Serdaliyevna; Khasanova Yulduz Mukhtor kizi (Bright Mind Publishing, 2025)
The growing trend of online education has resulted in a major transformation in the delivery of higher education. This research seeks to investigate how online education impacts the teaching of human sciences in higher education by analyzing its advantages and difficulties. The study's results indicate that online education positively influences higher education by enhancing accessibility, flexibility, and convenience. It enables students to access learning materials from any location at any time and to progress at their own speed. Additionally, it helps students manage their academic and personal responsibilities more efficiently. Nonetheless, challenges like limited social interaction, technical difficulties, and the need for self-discipline were noted as obstacles to successful online learning. The study was conducted using a quantitative method and collected opinions on online learning from 40 students from different human sciences subjects. The results show that online learning allows students to be more independent and manage their time more effectively, but it also leads to challenges in terms of communication and technology use between teachers and students. The study advocates for greater use of interactive teaching methods to increase student engagement, develop digital skills and improve online learning.
Keywords: Human sciences, online learning, flexibility, accessibility, social interaction, communication difficulties, quantitative studies, student participation, educational technology, self-regulation, instructional approaches, learning achievements.